A preparation process of nickel-based flux-cored welding wire

By preparing nickel-based flux-core welding wire and using materials such as carbon nanotube reinforced alloy powder, the problem of poor mechanical properties of nickel-based welding rod welds is solved, and the welding quality is improved and application strength is enhanced.

CN118180709BActive Publication Date: 2025-04-18JIANGSU JIUZHOU NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410492727.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2025-04-18
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

When welding nickel-based electrodes in existing nickel-based alloy structural parts, the tensile strength of the weld is poor under normal temperature and high temperature environment, which limits the application strength of nickel-based alloy welding structural parts.

Method used

The preparation process of nickel-based flux-core welding wire is adopted. By mixing nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon powder evenly and drying in vacuum, we obtain welding medicine, and the welding skin is rolled into a U-shaped shape, then sealed and rolled into an O-shaped shape, and finally wire drawing is carried out to make nickel-based flux-core welding wire.

Benefits of technology

It improves the mechanical properties of the weld under normal temperature and high temperature environment, reduces pores and inclusion defects during welding, enhances welding quality, and improves the application strength of nickel-based alloy welding structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118180709B_ABST
    Figure CN118180709B_ABST
Patent Text Reader

Abstract

The invention relates to the field of welding materials, and in particular to a preparation process of a nickel-based flux-cored welding wire, which is used to solve the problem that when an existing nickel-based welding rod is used to weld a nickel-based alloy, a weld formed has poor mechanical properties under normal and high temperature environments; the nickel-based flux-cored welding wire is composed of flux and welding skin, and the flux includes the following components: nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon micropowder; the raw materials used in the preparation process are reasonably compounded, so that the prepared nickel-based flux-cored welding wire has good welding performance, beautiful weld formation, stable welding joint performance, reduced pores and inclusion defects in the welding process, improved welding quality, and enhanced the mechanical properties of the weld.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of welding materials, and in particular to a preparation process of a nickel-based flux-cored welding wire. Background Art

[0002] With the development of industry, the demand for high temperature resistant and corrosion resistant materials is growing. Nickel-based alloys have been widely used in aerospace, petrochemical, marine engineering and other fields due to their excellent high temperature performance and corrosion resistance. For the welding of nickel-based alloy structural parts, the existing technology usually uses general nickel-based welding rods for welding. The room temperature tensile strength of the weld is about 550MPa, and its tensile strength under high temperature conditions is greatly reduced, far from the inherent strength of the parent material, which greatly limits the application strength of nickel-based alloy welded structural parts.

[0003] Therefore, how to improve the mechanical properties of the weld under normal and high temperature environments is the key to the present invention, and developing a preparation process for a nickel-based flux-cored welding wire has important practical value. Summary of the invention

[0004] In order to overcome the above technical problems, the purpose of the present invention is to provide a preparation process of nickel-based flux-cored welding wire: nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon micropowder are mixed uniformly and vacuum dried to obtain flux, the weld skin is rolled into a U-shape, the flux is added, and then the weld is sealed and rolled into an O-shape, and then wire drawing is performed to make a nickel-based flux-cored welding wire, which solves the problem of poor mechanical properties of the weld formed when the existing nickel-based welding rod is used to weld the nickel-based alloy under normal and high temperature environments.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A preparation process of a nickel-based flux-cored welding wire comprises the following steps:

[0007] Step 1: Weigh 38-46 parts of nickel powder, 13-17 parts of chromium powder, 5-11 parts of molybdenum powder, 3.7-8.3 parts of carbon nanotube reinforced alloy powder, 3.1-5.5 parts of aluminum powder, 2.6-4.8 parts of iron powder, 1.4-1.9 parts of calcium fluoride and 0.9-1.3 parts of silicon powder according to weight parts, and set aside;

[0008] Step 2: uniformly mix nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon powder and vacuum dry them to obtain welding flux;

[0009] Step 3: Roll the weld skin into a U shape, add flux, seal it and roll it into an O shape, then draw it to make a nickel-based flux-cored welding wire with a diameter of 3 mm.

[0010] As a further solution of the present invention: the carbon nanotube reinforced alloy powder is prepared by the following steps:

[0011] Step A1: titanium carbide powder, titanium powder and tungsten carbide are mixed uniformly to obtain a mixed powder, the mixed powder is added to a ball mill, and ball milled for 8-10 hours at a ball milling speed of 500-600 r / min and a ball-to-material ratio of 10-15:1 to obtain a ball mill, the ball mill is placed in a graphite mold, and then the temperature is increased to 1500-1600° C. at a heating rate of 80-100° C. / min and a pressure of 50 MPa, and then sintered for 10-20 minutes to obtain a high-strength alloy powder;

[0012] Step A2: adding carbon nanotubes and hydrochloric acid solution to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, ultrasonically dispersing for 25-30 minutes at an ultrasonic power of 200-300 W, stirring the reaction for 10-15 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then heating to reflux and continuing to stir the reaction for 3-5 hours, cooling the reaction product to room temperature after the reaction is completed, and then centrifuging, washing the precipitate with distilled water for 2-3 times, and then placing it in a vacuum drying oven and drying it at a temperature of 60-65° C. for 8-10 hours to obtain purified carbon nanotubes;

[0013] Step A3: Add the purified carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to reflux and continue stirring and reacting for 3-5 hours. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water for 2-3 times, then add it to anhydrous acetone and soak it for 1-2 hours, then centrifuge it, place the precipitate in a vacuum drying oven, and dry it at a temperature of 90-95°C for 3-5 hours to obtain acidified carbon nanotubes;

[0014] Step A4: adding acidified carbon nanotubes, thionyl chloride and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, introducing nitrogen protection, stirring the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 10-15 min, then heating to 70-75° C. and continuing to stir the reaction for 15-20 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with anhydrous tetrahydrofuran for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75° C. for 2-3 h to obtain chlorinated carbon nanotubes;

[0015] Step A5: adding acyl chloride carbon nanotubes, triethylenetetramine and deionized water into a three-necked flask equipped with a stirrer and a thermometer, stirring the mixture at a temperature of 110-115° C. and a stirring rate of 300-400 r / min for 25-30 hours, cooling the reaction product to room temperature after the reaction, and then centrifuging it. The precipitate is washed with anhydrous tetrahydrofuran for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75° C. for 4-5 hours to obtain amino carbon nanotubes;

[0016] Step A6: Add the amino carbon nanotubes, propylene oxide and N, N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a reflux condenser, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 10-15min, then raise the temperature to reflux and continue stirring the reaction for 4-5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with anhydrous tetrahydrofuran for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 40-45°C for 8-10h to obtain highly dispersed carbon nanotubes;

[0017] Step A7: Add high-strength alloy powder, highly dispersed carbon nanotubes and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically disperse for 25-30 minutes at an ultrasonic power of 200-300W, then stir and react for 60-65 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add to a ball mill, and ball mill for 15-20 hours at a ball mill speed of 500-600r / min and a ball-to-material ratio of 8-10:1 to obtain a ball mill slurry, centrifuge the ball mill slurry, place the precipitate in a graphite mold, and then heat to 600-650°C at a heating rate of 50-60°C / min and a pressure of 40MPa, and then sinter for 2-3 hours to obtain a carbon nanotube reinforced alloy powder.

[0018] As a further solution of the present invention: the nickel-based flux-cored welding wire includes welding flux and welding skin.

[0019] As a further solution of the present invention: the filling amount of the flux is 28-32% of the mass of the nickel-based flux-cored welding wire.

[0020] As a further solution of the present invention: the welding skin is a metal strip made of Ni 625 nickel-based alloy with a thickness of 0.3-0.35 mm.

[0021] As a further solution of the present invention: the usage ratio of the titanium carbide powder, titanium powder and tungsten carbide in step A1 is 10g:10g:10-20g.

[0022] As a further solution of the present invention: the usage ratio of the carbon nanotubes and the hydrochloric acid solution in step A2 is 1 g: 20-25 mL, and the molar concentration of the hydrochloric acid solution is 4-4.5 mol / L.

[0023] As a further solution of the present invention: the usage ratio of the purified carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step A3 is 1g:15-20mL:3-5mL, the mass fraction of the concentrated sulfuric acid is 98%, and the mass fraction of the concentrated nitric acid is 68%.

[0024] As a further solution of the present invention: the usage ratio of the acidified carbon nanotubes, thionyl chloride and N,N-dimethylformamide in step A4 is 1 g: 20-25 mL: 0.5-1 mL.

[0025] As a further solution of the present invention: the usage ratio of the chlorinated carbon nanotubes, triethylenetetramine and deionized water in step A5 is 1 g: 20-25 mL: 10-15 mL.

[0026] As a further solution of the present invention: the usage ratio of the amino carbon nanotubes, propylene oxide and N,N-dimethylformamide in step A6 is 1 g: 20-25 mL: 15-20 mL.

[0027] As a further solution of the present invention: the high-strength alloy powder, highly dispersed carbon nanotubes and anhydrous ethanol 10g: 0.1-0.5g: 100-120mL in step A7.

[0028] Beneficial effects of the present invention:

[0029] The invention discloses a preparation process of a nickel-based flux-cored welding wire, comprising the steps of uniformly mixing nickel powder, chromium powder, molybdenum powder, carbon nanotube-reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon micropowder and vacuum drying to obtain flux, rolling the weld skin into a U-shape, adding the flux, sealing and rolling into an O-shape, and then drawing to prepare the nickel-based flux-cored welding wire; the raw materials used in the preparation process are reasonably compounded, so that the prepared nickel-based flux-cored welding wire has good welding performance, beautiful weld formation, stable welding joint performance, reduced pores and inclusion defects in the welding process, improved welding quality, and enhanced mechanical properties of the weld;

[0030] In the process of preparing nickel-based flux-cored welding wire, a carbon nanotube-reinforced alloy powder is first prepared. First, titanium carbide powder, titanium powder and tungsten carbide are ball-milled and sintered to form an alloy to obtain a high-strength alloy powder. Then, the carbon nanotubes are treated with a hydrochloric acid solution to remove impurities thereon to obtain purified carbon nanotubes. Then, the purified carbon nanotubes are acidified with concentrated sulfuric acid and concentrated nitric acid to introduce carboxyl groups onto their surfaces to obtain acidified carbon nanotubes. Then, the acidified carbon nanotubes are chlorinated with thionyl chloride to obtain chlorinated carbon nanotubes. Then, the chlorinated carbon nanotubes are chlorinated with thionyl chloride to obtain chlorinated carbon nanotubes. The acyl chloride group on the carbon nanotube reacts with the amino group on the triethylenetetramine to introduce amino and secondary amine groups to obtain amino carbon nanotubes. Finally, the amino and secondary amine groups on the amino carbon nanotubes react with the epoxy groups on the propylene oxide to introduce a large number of hydroxyl groups to obtain highly dispersed carbon nanotubes. After that, the high-strength alloy powder and the highly dispersed carbon nanotubes are ball-milled together and finally sintered to obtain carbon nanotube-reinforced alloy powder. Titanium carbide has many excellent properties: high hardness, high melting point, wear resistance, and corrosion resistance. Tungsten carbide has high deformation resistance and flexural properties, as well as good impact resistance. It can withstand high temperatures at low temperatures. It can also maintain toughness and impact strength. Therefore, the alloy formed by the reasonable compounding of titanium carbide powder, titanium powder and tungsten carbide combines the advantages of the three to greatly improve its mechanical properties. Then, carbon nanotubes are added. The carbon nanotubes have a large aspect ratio, good tensile strength and elastic modulus, and can effectively improve the mechanical properties of the high-strength alloy powder, so that its strength and fracture toughness are further improved. In addition, carbon nanotubes also have the effect of reducing the friction coefficient and wear of ceramic materials, and carbon nanotubes have a high thermal conductivity. The addition of carbon nanotubes can effectively increase the thermal conductivity of the high-strength alloy powder, so that it still has high performance under high temperature conditions. At the same time, since the highly dispersed carbon nanotubes contain a large number of hydroxyl groups, they can be adsorbed with the molecules on the surface of the high-strength alloy powder material, which can effectively reduce the friction resistance in the ball milling process, reduce energy consumption, avoid agglomeration, and promote the ball milling effect, so that the high-strength alloy powder and the highly dispersed carbon nanotubes can be fully refined and mixed evenly with each other, so that the obtained carbon nanotube-reinforced alloy powder has excellent mechanical properties, and the enhancement effect on the nickel-based flux-cored welding wire is significant. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention will be further described below in conjunction with the accompanying drawings.

[0032] Figure 1 The present invention is a flow chart of a process for preparing a nickel-based flux-cored welding wire. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Embodiment 1:

[0035] See also Figure 1 As shown, this embodiment is a preparation process of a nickel-based flux-cored welding wire, comprising the following steps:

[0036] Step S1: 10 g of titanium carbide powder, 10 g of titanium powder and 10 g of tungsten carbide are mixed uniformly to obtain a mixed powder, the mixed powder is added to a ball mill, and the ball milling is performed for 8 h at a ball milling speed of 500 r / min and a ball-to-material ratio of 10:1 to obtain a ball mill material, the ball mill material is placed in a graphite mold, and then the temperature is increased to 1500° C. at a heating rate of 80° C. / min and a pressure of 50 MPa, and then sintered for 10 min to obtain a high-strength alloy powder;

[0037] Step S2: 1 g of carbon nanotubes and 20 mL of a hydrochloric acid solution with a molar concentration of 4 mol / L were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 25 min at an ultrasonic power of 200 W, and then stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 10 min, and then heated to reflux and continued to stir for reaction for 3 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 8 h to obtain purified carbon nanotubes;

[0038] Step S3: 1 g of purified carbon nanotubes, 15 mL of concentrated sulfuric acid with a mass fraction of 98%, and 3 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, and stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 10 min, then the temperature is raised to reflux and the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with distilled water, then added to anhydrous acetone and soaked for 1 h, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 90° C. for 3 h to obtain acidified carbon nanotubes;

[0039] Step S4: 1 g of acidified carbon nanotubes, 20 mL of thionyl chloride and 0.5 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 300 r / min for 10 min, and then the mixture was heated to 70° C. and the stirring reaction was continued for 15 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at 70° C. for 2 h to obtain chlorinated carbon nanotubes;

[0040] Step S5: 1 g of acyl chloride carbon nanotubes, 20 mL of triethylenetetramine and 10 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 110° C. and a stirring rate of 300 r / min for 25 h. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at a temperature of 70° C. for 4 h to obtain amino carbon nanotubes;

[0041] Step S6: 1 g of amino carbon nanotubes, 20 mL of propylene oxide and 15 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a reflux condenser, and nitrogen protection was introduced. The mixture was stirred for reaction at 25°C and a stirring rate of 300 r / min for 10 min, and then the temperature was raised to reflux and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at 40°C for 8 h to obtain highly dispersed carbon nanotubes;

[0042] Step S7: 10 g of high-strength alloy powder, 0.1 g of highly dispersed carbon nanotubes and 100 mL of anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 25 min under an ultrasonic power of 200 W, and then stirred for reaction for 60 min at a temperature of 25° C. and a stirring rate of 300 r / min, and then added to a ball mill, and ball milled for 15 h at a ball mill speed of 500 r / min and a ball-to-material ratio of 8:1 to obtain a ball milled slurry, the ball milled slurry is centrifuged, and the precipitate is placed in a graphite mold, and then heated to 600° C. at a heating rate of 50° C. / min and a pressure of 40 MPa, and then sintered for 2 h to obtain a carbon nanotube-reinforced alloy powder;

[0043] Step S8: Weigh 38 parts of nickel powder, 13 parts of chromium powder, 5 parts of molybdenum powder, 3.7 parts of carbon nanotube reinforced alloy powder, 3.1 parts of aluminum powder, 2.6 parts of iron powder, 1.4 parts of calcium fluoride and 0.9 parts of silicon powder according to weight parts for later use;

[0044] Step S9: uniformly mixing nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon powder and vacuum drying to obtain welding flux;

[0045] Step S10: rolling the weld skin into a U-shape, adding flux, then sealing and rolling it into an O-shape, and then drawing it to make a nickel-based flux-cored welding wire with a diameter of 3 mm; the nickel-based flux-cored welding wire includes flux and weld skin; the filling amount of the flux is 28% of the mass of the nickel-based flux-cored welding wire; the weld skin is a metal strip made of Ni 625 nickel-based alloy with a thickness of 0.3 mm.

[0046] Embodiment 2:

[0047] See also Figure 1 As shown, this embodiment is a preparation process of a nickel-based flux-cored welding wire, comprising the following steps:

[0048] Step S1: 10 g of titanium carbide powder, 10 g of titanium powder and 15 g of tungsten carbide are mixed uniformly to obtain a mixed powder, the mixed powder is added to a ball mill, and ball milled for 9 hours at a ball milling speed of 550 r / min and a ball-to-material ratio of 12:1 to obtain a ball mill, the ball mill is placed in a graphite mold, and then the temperature is increased to 1550° C. at a heating rate of 90° C. / min and a pressure of 50 MPa, and then sintered for 15 minutes to obtain a high-strength alloy powder;

[0049] Step S2: 1 g of carbon nanotubes and 22 mL of a hydrochloric acid solution with a molar concentration of 4.2 mol / L were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 28 min at an ultrasonic power of 250 W, and then stirred for reaction at a temperature of 28 ° C and a stirring rate of 350 r / min for 12 min, and then heated to reflux and continued to stir for 4 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 62 ° C for 9 h to obtain purified carbon nanotubes;

[0050] Step S3: 1 g of purified carbon nanotubes, 18 mL of concentrated sulfuric acid with a mass fraction of 98%, and 4 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 12 min, then heated to reflux and continued to stir for reaction for 4 h. After the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, the precipitate is washed twice with distilled water, then added to anhydrous acetone and soaked for 1.5 h, then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 92° C. for 4 h to obtain acidified carbon nanotubes;

[0051] Step S4: 1 g of acidified carbon nanotubes, 22 mL of thionyl chloride and 0.8 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 12 min, and then the mixture was heated to 72° C. and the stirring reaction was continued for 18 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at 72° C. for 2.5 h to obtain chlorinated carbon nanotubes;

[0052] Step S5: 1 g of acyl chloride carbon nanotubes, 22 mL of triethylenetetramine and 12 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 112° C. and a stirring rate of 350 r / min for 28 h. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at a temperature of 72° C. for 4.5 h to obtain amino carbon nanotubes;

[0053] Step S6: 1 g of amino carbon nanotubes, 22 mL of propylene oxide and 18 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a reflux condenser, and nitrogen protection was introduced. The mixture was stirred for reaction at 28° C. and a stirring rate of 350 r / min for 12 min, and then the mixture was heated to reflux and continued to stir for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at 42° C. for 9 h to obtain highly dispersed carbon nanotubes.

[0054] Step S7: 10 g of high-strength alloy powder, 0.3 g of highly dispersed carbon nanotubes and 110 mL of anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 28 min under an ultrasonic power of 250 W, and then stirred for reaction for 62 min at a temperature of 28 ° C and a stirring rate of 350 r / min, and then added to a ball mill, and ball milled for 18 h at a ball mill speed of 550 r / min and a ball-to-material ratio of 9:1 to obtain a ball milled slurry, the ball milled slurry is centrifuged, and the precipitate is placed in a graphite mold, and then heated to 625 ° C at a heating rate of 55 ° C / min and a pressure of 40 MPa, and then sintered for 2.5 h to obtain a carbon nanotube reinforced alloy powder;

[0055] Step S8: Weigh 42 parts of nickel powder, 15 parts of chromium powder, 8 parts of molybdenum powder, 6.0 parts of carbon nanotube reinforced alloy powder, 4.3 parts of aluminum powder, 3.7 parts of iron powder, 1.6 parts of calcium fluoride and 1.1 parts of silicon powder according to weight parts for later use;

[0056] Step S9: uniformly mixing nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon powder and vacuum drying to obtain welding flux;

[0057] Step S10: rolling the weld skin into a U-shape, adding flux, then sealing and rolling into an O-shape, and then drawing to make a nickel-based flux-cored welding wire with a diameter of 3 mm; the nickel-based flux-cored welding wire includes flux and weld skin; the filling amount of the flux is 30% of the mass of the nickel-based flux-cored welding wire; the weld skin is a metal strip made of Ni 625 nickel-based alloy with a thickness of 0.32 mm.

[0058] Embodiment 3:

[0059] See also Figure 1 As shown, this embodiment is a preparation process of a nickel-based flux-cored welding wire, comprising the following steps:

[0060] Step S1: 10 g of titanium carbide powder, 10 g of titanium powder and 20 g of tungsten carbide are mixed evenly to obtain a mixed powder, the mixed powder is added to a ball mill, and the ball milling is performed for 10 hours at a ball milling speed of 600 r / min and a ball-to-material ratio of 15:1 to obtain a ball mill material, the ball mill material is placed in a graphite mold, and then the temperature is increased to 1600° C. at a heating rate of 100° C. / min and a pressure of 50 MPa, and then sintered for 20 minutes to obtain a high-strength alloy powder;

[0061] Step S2: 1 g of carbon nanotubes and 25 mL of a hydrochloric acid solution with a molar concentration of 4.5 mol / L were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 30 min at an ultrasonic power of 300 W, and then stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, and then heated to reflux and continued to stir for reaction for 5 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 10 h to obtain purified carbon nanotubes;

[0062] Step S3: 1 g of purified carbon nanotubes, 20 mL of concentrated sulfuric acid with a mass fraction of 98%, and 5 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, then the temperature is raised to reflux and the stirring reaction is continued for 5 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with distilled water for 3 times, then added to anhydrous acetone and soaked for 2 h, then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 95° C. for 5 h to obtain acidified carbon nanotubes;

[0063] Step S4: 1 g of acidified carbon nanotubes, 25 mL of thionyl chloride and 1 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 400 r / min for 15 min, and then the mixture was heated to 75° C. and stirred for 20 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 3 times with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at 75° C. for 3 h to obtain chlorinated carbon nanotubes;

[0064] Step S5: 1 g of acyl chloride carbon nanotubes, 25 mL of triethylenetetramine and 15 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 115° C. and a stirring rate of 400 r / min for 30 h. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 3 times with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at a temperature of 75° C. for 5 h to obtain amino carbon nanotubes;

[0065] Step S6: 1 g of amino carbon nanotubes, 25 mL of propylene oxide and 20 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a reflux condenser, and nitrogen protection was introduced. The mixture was stirred for reaction at 30°C and a stirring rate of 400 r / min for 15 min, and then the mixture was heated to reflux and continued to stir for 5 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 3 times with anhydrous tetrahydrofuran, and then placed in a vacuum drying oven and dried at 45°C for 10 h to obtain highly dispersed carbon nanotubes.

[0066] Step S7: 10 g of high-strength alloy powder, 0.5 g of highly dispersed carbon nanotubes and 120 mL of anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 30 min at an ultrasonic power of 300 W, and then stirred for reaction for 65 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then added to a ball mill, and ball milled for 20 h at a ball mill speed of 600 r / min and a ball-to-material ratio of 10:1 to obtain a ball milled slurry, the ball milled slurry is centrifuged, and the precipitate is placed in a graphite mold, and then heated to 650° C. at a heating rate of 60° C. / min and a pressure of 40 MPa, and then sintered for 3 h to obtain a carbon nanotube-reinforced alloy powder;

[0067] Step S8: Weigh 46 parts of nickel powder, 17 parts of chromium powder, 11 parts of molybdenum powder, 8.3 parts of carbon nanotube reinforced alloy powder, 5.5 parts of aluminum powder, 4.8 parts of iron powder, 1.9 parts of calcium fluoride and 1.3 parts of silicon powder according to weight parts for later use;

[0068] Step S9: uniformly mixing nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon powder and vacuum drying to obtain welding flux;

[0069] Step S10: rolling the weld skin into a U-shape, adding flux, then sealing and rolling it into an O-shape, and then drawing it to make a nickel-based flux-cored welding wire with a diameter of 3 mm; the nickel-based flux-cored welding wire includes flux and weld skin; the filling amount of the flux is 32% of the mass of the nickel-based flux-cored welding wire; the weld skin is a metal strip made of Ni 625 nickel-based alloy with a thickness of 0.35 mm.

[0070] Comparative Example 1:

[0071] This comparative example is a preparation process of a nickel-based flux-cored welding wire, comprising the following steps:

[0072] Step S1: 10 g of titanium carbide powder, 10 g of titanium powder and 20 g of tungsten carbide are mixed evenly to obtain a mixed powder, the mixed powder is added to a ball mill, and the ball milling is performed for 10 hours at a ball milling speed of 600 r / min and a ball-to-material ratio of 15:1 to obtain a ball mill material, the ball mill material is placed in a graphite mold, and then the temperature is increased to 1600° C. at a heating rate of 100° C. / min and a pressure of 50 MPa, and then sintered for 20 minutes to obtain a high-strength alloy powder;

[0073] Step S2: Weigh 46 parts of nickel powder, 17 parts of chromium powder, 11 parts of molybdenum powder, 8.3 parts of high-strength alloy powder, 5.5 parts of aluminum powder, 4.8 parts of iron powder, 1.9 parts of calcium fluoride and 1.3 parts of silicon powder according to weight parts, and set aside;

[0074] Step S3: uniformly mixing nickel powder, chromium powder, molybdenum powder, high-strength alloy powder, aluminum powder, iron powder, calcium fluoride and silicon powder and vacuum drying to obtain welding flux;

[0075] Step S4: rolling the weld skin into a U-shape, adding flux, then sealing and rolling it into an O-shape, and then drawing it to make a nickel-based flux-cored welding wire with a diameter of 3 mm; the nickel-based flux-cored welding wire includes flux and weld skin; the filling amount of the flux is 32% of the mass of the nickel-based flux-cored welding wire; the weld skin is a metal strip made of Ni 625 nickel-based alloy with a thickness of 0.35 mm.

[0076] Comparative Example 2:

[0077] This comparative example is a preparation process of a nickel-based flux-cored welding wire, comprising the following steps:

[0078] Step S1: Weigh 46 parts of nickel powder, 17 parts of chromium powder, 11 parts of molybdenum powder, 8.3 parts of carbon nanotubes, 5.5 parts of aluminum powder, 4.8 parts of iron powder, 1.9 parts of calcium fluoride and 1.3 parts of silicon powder according to weight parts, and set aside;

[0079] Step S2: uniformly mixing nickel powder, chromium powder, molybdenum powder, carbon nanotubes, aluminum powder, iron powder, calcium fluoride and silicon powder and vacuum drying to obtain welding flux;

[0080] Step S3: rolling the weld skin into a U-shape, adding flux, then sealing and rolling it into an O-shape, and then drawing it to make a nickel-based flux-cored welding wire with a diameter of 3 mm; the nickel-based flux-cored welding wire includes flux and weld skin; the filling amount of the flux is 32% of the mass of the nickel-based flux-cored welding wire; the weld skin is a metal strip made of Ni 625 nickel-based alloy with a thickness of 0.35 mm.

[0081] Comparative Example 3:

[0082] This comparative example is a preparation process of a nickel-based flux-cored welding wire, comprising the following steps:

[0083] Step S1: 10 g of titanium carbide powder, 10 g of titanium powder and 20 g of tungsten carbide are mixed evenly to obtain a mixed powder, the mixed powder is added to a ball mill, and the ball milling is performed for 10 hours at a ball milling speed of 600 r / min and a ball-to-material ratio of 15:1 to obtain a ball mill material, the ball mill material is placed in a graphite mold, and then the temperature is increased to 1600° C. at a heating rate of 100° C. / min and a pressure of 50 MPa, and then sintered for 20 minutes to obtain a high-strength alloy powder;

[0084] Step S2: 10 g of high-strength alloy powder, 0.5 g of carbon nanotubes and 120 mL of anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 30 min under the condition of an ultrasonic power of 300 W, and then stirred for reaction for 65 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then added to a ball mill, and ball milled for 20 h at a ball mill speed of 600 r / min and a ball-to-material ratio of 10:1 to obtain a ball milled slurry, the ball milled slurry is centrifuged, and the precipitate is placed in a graphite mold, and then heated to 650° C. at a heating rate of 60° C. / min and a pressure of 40 MPa, and then sintered for 3 h to obtain a carbon nanotube reinforced alloy powder;

[0085] Step S3: Weigh 46 parts of nickel powder, 17 parts of chromium powder, 11 parts of molybdenum powder, 8.3 parts of carbon nanotube reinforced alloy powder, 5.5 parts of aluminum powder, 4.8 parts of iron powder, 1.9 parts of calcium fluoride and 1.3 parts of silicon powder according to weight parts for later use;

[0086] Step S4: uniformly mixing nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon powder and vacuum drying to obtain welding flux;

[0087] Step S5: rolling the weld skin into a U-shape, adding flux, then sealing and rolling it into an O-shape, and then drawing it to make a nickel-based flux-cored welding wire with a diameter of 3 mm; the nickel-based flux-cored welding wire includes flux and weld skin; the filling amount of the flux is 32% of the mass of the nickel-based flux-cored welding wire; the weld skin is a metal strip made of Ni 625 nickel-based alloy with a thickness of 0.35 mm.

[0088] The performance of Examples 1-3 and Comparative Examples 1-3 was tested. Two Ni625 nickel-based alloy plates were welded by a welding machine according to GB / T 17493-2008. The protective gas was 80% Ar + 20% CO2. After welding, the appearance of the weld was observed and mechanical tests were performed. The test results are shown in the following table:

[0089]

[0090] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the addition of high-strength alloy powder, carbon nanotubes and carbon nanotube-reinforced alloy powder can significantly improve the mechanical properties of nickel-based flux-cored welding wire, among which the nickel-based flux-cored welding wire with the addition of carbon nanotube-reinforced alloy powder in the embodiment of the present invention has the best performance.

[0091] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0092] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A process for preparing a nickel-based flux-cored welding wire, characterized in that: The following steps are involved: Step 1: Weigh 38-46 parts of nickel powder, 13-17 parts of chromium powder, 5-11 parts of molybdenum powder, 3.7-8.3 parts of carbon nanotube reinforced alloy powder, 3.1-5.5 parts of aluminum powder, 2.6-4.8 parts of iron powder, 1.4-1.9 parts of calcium fluoride and 0.9-1.3 parts of silicon powder according to weight parts, and set aside; Step 2: uniformly mix nickel powder, chromium powder, molybdenum powder, carbon nanotube reinforced alloy powder, aluminum powder, iron powder, calcium fluoride and silicon powder and vacuum dry them to obtain welding flux; Step 3: Roll the weld skin into a U shape, add flux, seal it and roll it into an O shape, and then draw it to make a nickel-based flux-cored welding wire with a diameter of 3 mm; The carbon nanotube reinforced alloy powder is prepared by the following steps: Step A1: uniformly mix titanium carbide powder, titanium powder and tungsten carbide to obtain a mixed powder, ball-mill the mixed powder to obtain a ball mill material, and sinter the ball mill material to obtain a high-strength alloy powder; the amount ratio of the titanium carbide powder, titanium powder and tungsten carbide in step A1 is 10g:10g:10-20g; Step A2: adding carbon nanotubes and hydrochloric acid solution into a three-necked flask for ultrasonic dispersion, and then stirring for reaction. After the reaction is completed, the reaction product is cooled, and then centrifuged, and the precipitate is washed and dried to obtain purified carbon nanotubes; the amount ratio of the carbon nanotubes and the hydrochloric acid solution in step A2 is 1g:20-25mL, and the molar concentration of the hydrochloric acid solution is 4-4.5mol / L; Step A3: adding purified carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid into a three-necked flask and stirring for reaction. After the reaction is completed, the reaction product is cooled, then centrifuged, the precipitate is washed and soaked, then centrifuged, and the precipitate is dried to obtain acidified carbon nanotubes; the amount ratio of the purified carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step A3 is 1g:15-20mL:3-5mL, the mass fraction of the concentrated sulfuric acid is 98%, and the mass fraction of the concentrated nitric acid is 68%; Step A4: adding acidified carbon nanotubes, thionyl chloride and N,N-dimethylformamide into a three-necked flask and stirring for reaction. After the reaction is completed, the reaction product is cooled, then centrifuged, and the precipitate is washed and dried to obtain chlorinated carbon nanotubes; the amount ratio of the acidified carbon nanotubes, thionyl chloride and N,N-dimethylformamide in step A4 is 1g:20-25mL:0.5-1mL; Step A5: adding chlorinated carbon nanotubes, triethylenetetramine and deionized water into a three-necked flask and stirring for reaction. After the reaction is completed, the reaction product is cooled, then centrifuged, and the precipitate is washed and dried to obtain amination carbon nanotubes; the amount ratio of chlorinated carbon nanotubes, triethylenetetramine and deionized water in step A5 is 1g:20-25mL:10-15mL; Step A6: adding the aminated carbon nanotubes, glycidol and N,N-dimethylformamide into a three-necked flask and stirring for reaction. After the reaction is completed, the reaction product is cooled, then centrifuged, and the precipitate is washed and dried to obtain highly dispersed carbon nanotubes; the amount ratio of the aminated carbon nanotubes, glycidol and N,N-dimethylformamide in step A6 is 1g:20-25mL:15-20mL; Step A7: Add high-strength alloy powder, highly dispersed carbon nanotubes and anhydrous ethanol to a three-necked flask for ultrasonic dispersion, then stir to react, then ball mill to obtain ball-milled slurry, centrifuge the ball-milled slurry, and then sinter to obtain carbon nanotube-reinforced alloy powder; the high-strength alloy powder, highly dispersed carbon nanotubes and anhydrous ethanol in step A7 are 10g: 0.1-0.5g: 100-120mL.

2. The process for preparing a nickel-based flux-cored welding wire according to claim 1, characterized in that: The nickel-based flux-cored welding wire comprises welding flux and welding skin; The filling amount of the flux is 28-32% of the mass of the nickel-based flux-cored welding wire; The welding skin is a metal strip made of Ni 625 nickel-based alloy with a thickness of 0.3-0.35 mm.

Citation Information

Patent Citations

  • Powder metallurgy preparation method for high-strengthening-toughening metal-based composite material

    CN108080644A

  • Systems and methods for additive manufacturing using aluminum metal-cored wire

    CN111715974A

  • High-toughness nickel-based alloy flux-cored wire and preparation method thereof

    CN116352306A